2013
DOI: 10.1007/s10151-013-0998-7
|View full text |Cite
|
Sign up to set email alerts
|

Intracorporeal ileocolic anastomosis: a review

Abstract: This study is a narrative review of the current literature regarding intracorporeal ileocolic anastomosis in laparoscopic right colon resection for benign or malignant diseases of the right colon and terminal ileum. The search strategy included Medline, Embase, CINAHL, ACP Journal Club, and Cochrane databases with laparoscopic right colectomy and intracorporeal anastomosis as keywords. All retrieved references were screened by two independent blinded reviewers. Thirteen papers including 611 patients undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 16 publications
3
31
0
4
Order By: Relevance
“…In particular, no significant difference with respect to technical complication, such as the anastomotic leak rate, was observed. Similar results were reported by 4 recent meta-analyses, comparing the 2 surgical techniques in the nonobese population [8][9][10][11][12]. This finding is most likely multifactorial [8][9][10][11][12]14].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In particular, no significant difference with respect to technical complication, such as the anastomotic leak rate, was observed. Similar results were reported by 4 recent meta-analyses, comparing the 2 surgical techniques in the nonobese population [8][9][10][11][12]. This finding is most likely multifactorial [8][9][10][11][12]14].…”
Section: Discussionsupporting
confidence: 78%
“…with extensive experience in open and LPS colorectal surgery and familiar with both anastomosis techniques performed all the operations [8,9]. Patients underwent LPS right colectomy with IA or EA depending on surgeon's or patient's preference.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Within the literature, the designation of antiperistaltic versus isoperistaltic anastomoses is infrequently described; however, there is one important consequence that must be considered. The authors prefer antiperistaltic anastomoses, as the focus should be to unalter the rotation of the mesentery with the goal to prevent torsion [8][9][10][11]. Furthermore, a randomized controlled trial concluded that anastomotic leakage occurred only in patients with isoperistaltic anastomoses as compared to antiperistaltic [12].…”
mentioning
confidence: 99%
“…По некоторым данным, полностью лапароскопические операции позволяют достичь меньшего послеоперационного койко-дня по сравнению с операциями с форми-рованием экстракорпорального анастомоза. Также при этих операциях снижается необходимость ис-пользования наркотических анальгетиков и уско-ряются сроки реабилитации [14,15]. Однако пол-ностью лапароскопические операции не получили широкого распространения, поскольку требуют тщательного отбора пациентов, а для достижения преимуществ они должны выполняться очень опыт-ными лапароскопическими хирургами.…”
unclassified
“…Однако пол-ностью лапароскопические операции не получили широкого распространения, поскольку требуют тщательного отбора пациентов, а для достижения преимуществ они должны выполняться очень опыт-ными лапароскопическими хирургами. Кроме того, этот вид оперативных вмешательств ограничен сво-ей высокой стоимостью, поскольку формирование анастомоза в подавляющем большинстве случаев производится при помощи сшивающих аппаратов [9,[13][14][15][16]. Таким образом, в основном применя-ются лапароскопически-ассистированные вмеша-тельства.…”
unclassified